Biomass yield and growth allometry of some crops growing under weed stress (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Qadir S, Khan A, Salam IU. 2020. Biomass yield and growth allometry of some crops growing under weed stress. Biodiversitas 21: 5621-5629. The conventional approach in crop science generally focuses on nutritional yield of crops. Crop yield is basically ranked by its photosynthetic efficiency. Hence the higher reserves of photosynthetic products are achieved in the form of biomass. Current study explains the gain and loss in biomass of five different crops viz, Zea mays L. (maize), Hordeum vulgare L. (barley), Cicer arietinum L. (chickpea), Pisum sativum L. (pea) and Phaseolus vulgaris L. (French beans) treated by weed manure of Portulaca oleracea L., Euphorbia hirta L. and Amaranthus viridis L. at 5%, 10% and 15% concentration. The inhibitory effects of the given weeds persist with significant (p < 0.5) differences in the biomass of tested crops. Absolute growth rate (AGR), relative growth rate (RGR) and carbon content are highest (29.43 mg day-1, 2.43 mg gm-1day-1 and 15.25% respectively) in Chickpea plants induced by 5% P. oleracea extract. The highest inhibition recorded in Pea plants induced by 15% of A. viridis extract with 8.33 mg day-1, 1.42 mg gm-1day-1 and 4.67% of AGR, RGR and carbon yield respectively. Inhibition rate of weeds on leaf growth indices also exists in the same order i.e., the highest in A. viridis and the lowest in P. oleracea. Therefore, it is concluded that A. viridis has produced the highest level of inhibition among the three weeds while Pea species is the most sensitive crop species among the five tested crops.
Keywords: Absolute growth rate, Relative growth rate, growth indices, biomass, allelopathy